2017
DOI: 10.1107/s2052252517005577
|View full text |Cite
|
Sign up to set email alerts
|

Regulating thermosalient behaviour in three polymorphs

Abstract: Dynamic molecular crystals can be defined as crystalline materials that respond to external stimuli with mechanical responses on a macro-, micro-or nanoscopic scale (Naumov et al., 2015). The motility of dynamic crystals is usually triggered by a phase transition or chemical reaction without gaseous products, subsequently creating local stresses in the densely packed crystal lattice of the respective material (Commins et al., 2016). The amplification of such strain via cooperative processes can lead to reversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…[49] These exciting results demonstrated the potential of organic thermosalient crystals to actually work as energy converters, actuators, or other dynamic components, [50] which have been further clarified by a number of recently reported examples on thermosalient organic crystals. [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] Crystals of organic macrocycle compounds have been also explored as thermomechanical SCSC phase transition materials. [68][69][70][71] Very recently, Nishihara and co-workers reported a disilanyl macrocycle compound C4 that exhibited a mechanical motion in a reversible thermal-induced SCSC phase transition.…”
Section: Thermomechanical Energy Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…[49] These exciting results demonstrated the potential of organic thermosalient crystals to actually work as energy converters, actuators, or other dynamic components, [50] which have been further clarified by a number of recently reported examples on thermosalient organic crystals. [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] Crystals of organic macrocycle compounds have been also explored as thermomechanical SCSC phase transition materials. [68][69][70][71] Very recently, Nishihara and co-workers reported a disilanyl macrocycle compound C4 that exhibited a mechanical motion in a reversible thermal-induced SCSC phase transition.…”
Section: Thermomechanical Energy Conversionmentioning
confidence: 99%
“…[ 49 ] These exciting results demonstrated the potential of organic thermosalient crystals to actually work as energy converters, actuators, or other dynamic components, [ 50 ] which have been further clarified by a number of recently reported examples on thermosalient organic crystals. [ 51–67 ]…”
Section: Energy Conversion In Scsc Phase Transition Materialsmentioning
confidence: 99%
“…The strain is then released in a short time, resulting in crystal jumping . Thermosalient effects are caused by a packing structure change with , or without a thermal phase transition upon the temperature change. This structural alternation generates strain within the crystal.…”
Section: Introductionmentioning
confidence: 99%
“…Mittapalli et al reported polymorphs of the halogensubstituted N-salicylideneaniline derivatives which show different thermosalient responses such as jumping (Forms I and III) and exploding (Form II) in its three polymorphs during phase transition at high temperature. 49,50 This was a unique example of a combination of mechanophysical responses in a polymorphic compound. The structural dynamics of the thermosalient behavior in different polymorphs was correlated with the packing structure and weak C−Cl•••O halogen bond interactions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This study demonstrated the utility of hydrogen and halogen bonds in exhibiting the thermosalient effect of molecular crystals. 49,50 Recently, Matsumoto et al reported two polymorphs of a propylated diketopyrrolopyrrole dye where one polymorph (yellow form) showed thermosalient behavior upon heating. 51 The molecular conformation and the disordered propyl groups in the yellow form lead the heatstimulated mechanical response.…”
Section: ■ Introductionmentioning
confidence: 99%